SOSIALISASI PENCEGAHAN PERNIKAHAN USIA DINI MENURUT UU NO 16 TAHUN 2019 PADA WARGA DUSUN POSONG, KARANGTENGAH, WONOGIRI - ERIK WIDODO; WISNU SANJAYA (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
This paper aims at prevention efforts that have been carried out by extension to the community and the impact of this early marriage, and the factors that cause it and its impact, and how society views it that has an impact on the future. This research is a qualitative field research (field research). with a normative approach, sociological research shows that: 1) prevention efforts Early marriages, among others, organize outreach in the form of counseling about the impact early marriage to the future of the child. Raising public support, and encouraging establishment of regulations on the prevention and elimination of child marriage under 18 years of age. Forming a movement community to stop child marriage; 2) causes of early marriage among others, economic factors, family, promiscuity and low levels of education an impact on the increasing number of children dropping out of school, especially girls, violence against women, maternal and infant mortality; 3) the community responds positively to efforts to prevent child abuse from having an impact on the future; 4) the salvation of the soul is more important than the desire to acquire inheritance. So that government support is needed to further strengthen preventive measures and understanding to the community to prevent early childhood.